(untitled) (KULT_online, 2024)
Gut Anthro: An Experiment in Thinking with Microbes provides an opportunity and case study to bridge the gap between anthropology and human microbial ecology. Through fieldwork in laboratories, Bangladeshi hospitals, and the homes of families, the book gives insight into the connection between microbiomes and race as tangible expressions of society, environment, and biology. Amber Benezra examines how the biological-social disruptions cause problems, as well as the frictions of disciplinary collaboration, to rethink the meaning of relationship.